2009
DOI: 10.1007/s00294-009-0244-z
|View full text |Cite
|
Sign up to set email alerts
|

PTR1-dependent synthesis of tetrahydrobiopterin contributes to oxidant susceptibility in the trypanosomatid protozoan parasite Leishmania major

Abstract: Leishmania must survive oxidative stress, but lack many classical antioxidant enzymes and rely heavily on trypanothione-dependent pathways. We used forward genetic screens to recover loci mediating oxidant resistance via overexpression in Leishmania major, which identified pteridine reductase 1 (PTR1). Comparisons of isogenic lines showed ptr1 -null mutants were 18-fold more sensitive to H 2 O 2 than PTR1-overproducing lines, and significant 3-5 fold differences were seen with a broad panel of oxidant-inducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 71 publications
1
22
0
Order By: Relevance
“…Unlike humans and most other organisms that have monofunctional proteins, trypanosomatids express a bifunctional DHFR-TS in which a single polypeptide chain contains both catalytic activities [80]. DHFR-TS and PTR1, have been proposed as key drug targets in trypanosomatids because folates are essential for synthesis of thymidylate while pterins are implicated in parasites growth and oxidant resistance [81, 82]. …”
Section: Pteridine Metabolismmentioning
confidence: 99%
“…Unlike humans and most other organisms that have monofunctional proteins, trypanosomatids express a bifunctional DHFR-TS in which a single polypeptide chain contains both catalytic activities [80]. DHFR-TS and PTR1, have been proposed as key drug targets in trypanosomatids because folates are essential for synthesis of thymidylate while pterins are implicated in parasites growth and oxidant resistance [81, 82]. …”
Section: Pteridine Metabolismmentioning
confidence: 99%
“…2.5 ). These two enzymes have been proposed as drug targets in trypanosomatids, since they participate in essential pathways for the parasite metabolism, like thymidylate production by folates and oxidant resistance by the reduction of pterins (Moreira et al 2009 ;Nare et al 2009 ). Drugs that have been used to inhibit DHFR have proven ineffective in Leishmania (Neal and Croft 1984 ).…”
Section: Pteridine Metabolismmentioning
confidence: 98%
“…One of the earliest known cellular functions of THB was as a growth factor for the parasite Crithidia fasciculata [12], and many studies have indicated that THB is indeed an essential growth factor for Leishmania [13][14][15][16], although its exact role is still to be discovered (reviewed in [17]). THB was also shown to react readily with oxygen, superoxide, H 2 O 2 , and peroxynitrite and it was demonstrated that it protects cells against oxidative damages [18,19] (and reviewed in [20,21]). PTR1 and reduced pterins thus play important roles in Leishmania differentiation and life cycle in which the infective metacyclic form encounters an impressive oxidative stress as it meets with the host immune system.…”
Section: Introductionmentioning
confidence: 97%